Validity of the V-cut test for young basketball players - Gonzalo-Skok, O.; Tous-Fajardo, J.; Suarez-Arrones, L.; Arjol-Serrano, J. L.; Casajus, J. A.; Mendez-Villanueva, A. (International Journal of Sports Medicine, 2015)
The aim of the present study was to assess the reliability, usefulness, validity, age-related differences and responsiveness of a 25-?m side-step cutting maneuver test (V-cut test). Fifty young male basketball players performed the V-cut test on 2 occasions separated by 5-7 days to assess test-retest reliability and determine a priori usefulness. Twenty subjects also completed both the L-Run and 505 test to analyze the possible relationships among these 3 tests. Furthermore, 33 players performed the V-cut test 4 times throughout the season to analyze responsiveness. Finally, 53 players (U-14 to U-20) were assessed in the V-cut test to examine the age-related differences. Reliability scores showed high intraclass correlation coefficient (ICC=0.90) and low coefficient of variation (CV=1.4%). The responsiveness of the V-cut test was good, as the typical short- (1.5-1.7%), mid- (1.6-3.1%) and long-term (3.3%) changes in V-cut performance were higher than the CV. Low (r=0.64; CL90%: 0.34; 0.82) to moderate (r=0.76; CL90%: 0.53; 0.88) relationships were found between the V-cut test with the 505 and L-Run test, respectively. Age-related differences analysis showed better V-cut test performance as age increased in adolescent basketball players. The V-cut test is reliable to assess change of direction ability (CODA) and it could be used to monitor CODA in adolescent basketball players.